2017
DOI: 10.1007/s00520-016-3557-8
|View full text |Cite
|
Sign up to set email alerts
|

Association between bone scan index and activities of daily living in patients with advanced non-small cell lung cancer

Abstract: The results suggest that a high BSI (≥1.0) is an independent predictor of poor ADL in patients with NSCLC, while showing no correlation with the overall survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In our study, we roughly reproduced the published results [15,19,24] in terms of sensitivity in prostate (93%) and breast cancer (86%), but we observed a lower sensitivity in lung cancer (69%). The reference data of the tool used by Koizumi et al [24] (BONENAVI tool, version 2, Fujifilm RI Pharma Co. Ltd., Tokyo, Japan), used for training the specific network, also included bone scans from patients with lung cancer [22,33,35], whereas the software version (EXINI bone V2.1) used here does not. We hypothesized that the higher sensitivity of the alternative software tool is related to the deviating training database with respect to the specific tumor biology of lung cancer (e.g., osteolytic character of metastases).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we roughly reproduced the published results [15,19,24] in terms of sensitivity in prostate (93%) and breast cancer (86%), but we observed a lower sensitivity in lung cancer (69%). The reference data of the tool used by Koizumi et al [24] (BONENAVI tool, version 2, Fujifilm RI Pharma Co. Ltd., Tokyo, Japan), used for training the specific network, also included bone scans from patients with lung cancer [22,33,35], whereas the software version (EXINI bone V2.1) used here does not. We hypothesized that the higher sensitivity of the alternative software tool is related to the deviating training database with respect to the specific tumor biology of lung cancer (e.g., osteolytic character of metastases).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, due to false-positive ratings of areas of increased uptake, the BSI methodology is limited in the staging of patients with newly diagnosed prostate cancer [19]. BSI was evaluated thoroughly in prostate cancer, and some data on its performance in breast and lung cancer [20][21][22][23][24][25] are also available. Further validations of the methodology, e.g., for further tumor entities, are lacking.…”
Section: Introductionmentioning
confidence: 99%
“…We appreciate the interest shown by Dr. Shadmani and his colleagues in our recently published article entitled BAssociation between the bone scan index and activities of daily living in patients with advanced non-small cell lung cancer [1]^and his critical comments and useful suggestions [2].…”
mentioning
confidence: 97%
“…The authors aimed to study the association between the bone scan index (BSI) and activities of daily living (ADL) in patients with advanced nonsmall cell lung cancer (NSCLC). It was concluded that a higher value of the BSI (≥1.0) is an independent predictor of poor ADL in patients with advanced NSCLC [1]. However, although this was a valuable investigation and its findings were very interesting, some methodological issues should be considered.…”
mentioning
confidence: 99%
“…First, Suzanne Ikuno Ito et al [1] evaluated the predictor of elevated higher value of the BSI (≥1.0) in a cross-sectional study, whereas longitudinal studies are most important for making assumptions for clinical prediction models [2]. In other words, the temporality assumption (the dependent variable has to occur after the independent variable) must be ensured in the prediction model.…”
mentioning
confidence: 99%